MOTIVATION PSYCHOLOGY AND EMPLOYEE PERFORMANCE IN THE MANUFACTURING SECTOR OF JORDAN - Adnan M. Rawashdeh, Mohammad Salameh Almasarweh, Mahmoud Barakat Alnawaiseh (Chelonian Research Foundation, 2023)
Motivation has been examined and confirmed as one of the factors that linked employees to their firms. Further, motivation leads to positive employee performance. Hence, the main aim of this work is to examine the role of motivation practices in enhancing employee performance at manufacturing industry in Jordan. The data for this research were collected using self-structured questionnaire from 314 managers in the strategic, tactical, and operational management levels who were randomly selected from manufacturing companies in Amman, Jordan. Four hypotheses have been developed through literature review and tested using descriptive statistical analysis performed by SPSS. The results show a significant relationship between motivation factors that include training, monetary rewards, promotion, and working conditions and employee performance. To the best of our knowledge, this is the first study to develop a model for motivation in a manufacturing industry in Jordan. The firm management should consider these factors as a very important factors for promoting employee performance among employees in the manufacturing industry. Keywords: motivation, training, financial rewards, promotion, working conditions, employee performance, manufacturing industry, Jordan.